2010
DOI: 10.2460/ajvr.71.11.1348
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of pelvic tilt in the coronal plane on the Norberg angle measured in ventrodorsal radiographic views of a canine hip joint bone model

Abstract: Model-derived results indicated that pelvic tilt during acquisition of ventrodorsal radiographic views of the hip joints of a dog should not affect measurement of the NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The slight differences in repeated radiographs may derive from a combination of various factors such as the forces applied, pelvic tilting, muscle relaxation, central beam position or other unknown random effects. 20,24,25 The ICC showed minimally better results for the intra-and interobserver-reliability of the DI compared with the NA. This complies with a recent study where variability of the NA was higher than of the DI.…”
Section: Discussionmentioning
confidence: 95%
“…The slight differences in repeated radiographs may derive from a combination of various factors such as the forces applied, pelvic tilting, muscle relaxation, central beam position or other unknown random effects. 20,24,25 The ICC showed minimally better results for the intra-and interobserver-reliability of the DI compared with the NA. This complies with a recent study where variability of the NA was higher than of the DI.…”
Section: Discussionmentioning
confidence: 95%
“…In veterinary literature, we can find reports that highlight the importance of positioning during radiographic evaluations of skeletal morphology and implant positioning (26). It has been reported that the degree of pelvic tilt (malposition along the short axis of the pelvis) that occurs during the positioning of dogs to obtain a standard radiograph in the ventrodorsal hip extended view can range from zero degrees to -33° (26). However, any greater rotations would be clear and would probably lead to the patient being repositioned and the examination repeated.…”
Section: Parametermentioning
confidence: 99%
“…Factors such as age, sedation or anaesthesia, osteoarthritis (Vandekerckhove et al 2003;Gold et al 2009) and pelvic rotation may influence NA scores (Genevois et al 2007;Skurkova et al 2010). In a previous study, using a canine-bone model with changes of between 0° and 30° of pelvic rotation along the short body axis, the NA in VDHE views did not change (Bausman and Wendelburg 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Radiographic assessment and measurements on the standard VDHE view are the basis of the main international HD scor- Veterinarni Medicina, 62, 2017 (07): 377-385 doi: 10.17221/127/2016-VETMED ing systems: FCI, OFA and BVA/KC (Genevois et al 2007;Skurkova et al 2010;Chalmers et al 2013). Therefore, proper positioning and optimal exposure technique are essential prerequisites for radiographs of sufficient diagnostic quality to allow accurate HD assessment (Genevois et al 2007;Thompson et al 2007;Bausman and Wendelburg 2010). Pelvic rotation over the longitudinal axis changes hip radiographic morphology (Genevois et al 2007;Volta et al 2013;Martins et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation